Retention and Adaptation of two 3D-Printed Denture Base resins : A Comparative In Vitro Study - Abdulrahman, Hana Salam; Ameen Hasan, Rizgar Mohammed (Journal of Neonatal Surgery, 2025)
Objective: This study aims to evaluate the retention and adaptation characteristics of two 3D-printed denture base resins—Saremco Print DentureTec and Detax Freeprint Denture—fabricated using Digital Light Processing (DLP) technology. To standardize artificial saliva distribution and controlled force application, a printed key made from Detax Freeprint Model resin was introduced. Institutional Review Board Statement: This study was conducted in accordance with the ethical standards of Hawler Medical University. Ethical approval was obtained from the Scientific Research Ethical Committee, College of Dentistry, Hawler Medical University, Kurdistan Region, Iraq (Reference Number: HMUD,2425103; Date of Approval: 14 January 2025). Materials and methods: A total of 40 denture base samples (20 per resin type) were fabricated under standardized DLP printing parameters. Retention was assessed using a universal testing machine (UTM) to measure dislodging force in Newtons (N). Adaptation was evaluated via the silicone replica technique, with replica thickness measured using a digital micrometer. Artificial aging was simulated through thermal cycling (2500 cycles at 5°C–55°C). The printed key was utilized in retention and adaptation testing to ensure uniform conditions across trials. Statistical analyses included paired t-test. Results: Post-aging retention force increased significantly (p < 0.001) across both materials. Detax Freeprint Denture initially exhibited higher retention, but after aging, its performance aligned with Saremco Print DentureTec. Adaptation remained clinically acceptable, with minor dimensional changes after thermal cycling. The printed key improved experimental accuracy by minimizing variability in saliva distribution and force application. Conclusion: Retention improved due to polymer relaxation, while adaptation remained stable, supporting the clinical viability of 3D-printed denture bases. The printed key introduced a standardized methodology, enhancing precision and refining future research protocols.